Mummies at the mall - Herman, Gail, 1959-; Duendes Del Sur (Firm) (New York : Advance Publishers, 2006)
While Scooby and Shaggy are at the mall eating everything in sight, they see someone (or something) very scary running around. It looks like a mummy, but is it?
"Collect bonus pages to make your own Scooby-Doo mystery"--Cover.
"Read & solve volume 2"--Cover.
Bonus story-related activities included.
Keywords: Detective and mystery stories -- Juvenile fiction; Dogs -- Juvenile fiction; Mummies -- Juvenile fiction; Shopping malls -- Juvenile fiction